Deciphering drivers of using ICT among academia of agricultural sciences - PANDEY, D K; ADHIGURU, P; KUMAR, PRABHAT; HAZARIKA, B N (The Indian Journal of Agricultural Sciences, 2020)
Across the globe, investment in ICT to improve teaching and learning in educational institutions have been initiated by Governments. Despite all these investments on ICT infrastructure, equipment and professional development to improve education in many countries, ICT adoption and integration in teaching and learning have so far been limited. This paper investigates the factors influencing the usage of ICT tools among academia of agricultural sciences in north eastern hill states of India which is landlocked and poorly connected with the outside world. ICT can play a crucial role in overcoming its geographical exclusion and help in developing its human resource globally competitive. Slow internet speed and poor ICT infrastructure were reported as principal factors that severely affect the usage of ICT tools among the academia of agricultural sciences in north eastern hill states of India. Level of competency of teachers on ICT is also identified as a barrier. A few key measures to overcome these impediments and for facilitating greater usage of ICT in education are suggested. The findings of this study would be of practical importance to the academic administrators and civil society organizations whose aim is to provide quality higher education by integrating costeffective capabilities of ICT in teaching and learning.